Effectiveness of 96% Ethanol Extract of Clove Leaves (Syzygium aromaticum (L.) Merr & Perry) as an Antibacterial Agent Against Staphylococcus epidermidis And Providencia stuartii - Listiana Masyita Dewi; Muhjatul Qolbi Nafi’ah (Universitas Muhammadiyah Semarang, 2022)
Background: The incidence of antibiotic resistance as a consequence of antibiotic abuse becomes a barrier in accessing effective care. The ability of bacteria to form biofilms is an internal factor that can prevent contact between bacteria and antibiotic agents, such as Staphylococcus epidermidis and Providencia stuartii. The use of plant extracts as an antibiotic is thought to be a promising solution. One of the plants that can be used as an antibiotic is the clove (Syzygium aromaticum (L.) Merr & Perry).Objective: This study aims to determine the effectiveness of 96% ethanol extract of clove leaves (Syzygium aromaticum (L.) Merr & Perry) as an antibacterial agent against Staphylococcus epidermidis and Providencia struartii.Methods: This was an experimental analytic study with a post-test only control group design method on 4 treatment groups with a concentration of 2.5%; 5%; 10%; and 20%, as well as a positive control group and a negative control group, with 6 times repetition for each germ. Data analysis used the Kruskal Wallis test and the Post Hoc Mann Whitney test.Results: The results of the Kruskal Wallis test on the two research germs obtained p value <0.05. Post Hoc Mann Whitney test results, for the two research germs, the comparison of the data of each concentration to the negative control obtained p value <0.05.Conclusion: 96% ethanol extract of clove leaves has been shown to act as an antibacterial agent against Staphylococcus epidermidis and Providencia stuartii, and is stronger than chloramphenicol, but weaker when compared to ciprofloxacin